PENGARUH PENGELOLAAN KELAS TERHADAP HASIL BELAJAR SISWA PELAJARAN IPS MTs TADRISUL ULUM KUBU PADI - Deviani yarso; Sri Buwono; Husni Syahrudin (Universitas Tanjungpura, 2019)
Abstract This research aimed to know “the effect of classroom management towards 8th grade students learning outcomes in MTs Tradisul Ulum Kubu Padi.” This research addresses two problems: how are the 8th grade students’ social science learning outcomes in MTs Tadrisul Ulum Kubu Padi, does classroom management significantly affect the students’ learning outcomes in Social Science class, The methodology implemented was descriptive quantitative in a form of correlational study. The variables of the research included independent and dependent variables: classroom management as the independent variable and students’ learning outcomes as the dependent variable. The data of this research were taken from social science learning outcomes of the students taken from 40 students of the 8th grade who acted as the population of the study. The data were collected by using indirect communication and documentary study technique, using questionnaire as the tool. Based on the data analysis, the regression equation was Y = 57.641 + 0.342 X. From the T-test, it can be identified that the significance level (2-tailed) was 0.000 < 0.05), and the normality test determined the significance value of 0.769 > 0.05, meaning the residuals are distributed normally, and the percentage of the effect being 3.5% (low). Keywords: Classroom Management, Learning Outcomes